Pengembangan Website Pemasaran Jasa Konstruksi menggunakan Pendekatan Goal-Directed Design (GDD). Studi Kasus: CV. Krisna Dwi Karya - Ayu Puspita Rachmi; Hanifah Muslimah Az-Zahra; Bondan Sapta Prakoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
CV. Krisna Dwi Karya is one of the construction companies that impacted by business competition which makes it difficult for companies to get projects. It's because the lack of human resources in the marketing field that makes the companies carry out sober promotion without doing research about the information that the client's needed. Besides that, the information that given out are unstructured and without a proper concept so the audience having a trouble to find information about the companies. Therefore, a digital marketing media in form of a website is needed to introduce companies by providing a structured information to give a good experience for users. The Goal - Directed Design (GDD) method which has 6 stages was chosen because it has an orientation towards goals and user experience. This research also conducted the preparation of information architecture using card sorting, sitemap, and tree testing to obtain structured information. Then, testing of the website is carried out using usability testing as the qualitative test and Post - Study System Usability Questionnaire (PSSUQ) as the quantitative test. In usability testing, only 2 tasks out of a total of 10 tasks were failed by the respondents. While from the PSSUQ questionnaire, this website gets a score of 1,79 on the overall scale aspect, a score of 1,61 on the sysuse scale aspect, a score of 1,53 on the infoqual scale aspect, and a score of 2,33 on the interqual scale aspect.